(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
What is inclusion - An environment where everyone has an opportunity to fully participate, everyone has the same opportunity, there should be no boundaries such as ethnicity, gender and disability all should feel valued mix and participate with all members of the group.